2018
DOI: 10.3904/kjim.2017.377
|View full text |Cite
|
Sign up to set email alerts
|

Updated treatment strategies for intestinal Behçet’s disease

Abstract: Behçet’s disease (BD) is a chronic, idiopathic, relapsing immune-mediated disease involving multiple organs, and is characterized by recurrent oral and genital ulcers, ocular disease, gastrointestinal ulcers, vascular diseases, and skin lesions. In particular, gastrointestinal involvement in BD is followed by severe complications, including massive bleeding, bowel perforation, and fistula, which can lead to significant morbidity and mortality. However, the management of intestinal BD has not yet been properly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 106 publications
0
26
0
1
Order By: Relevance
“…[14,15] In 2015, ADa was approved for treatment of intestinal BD in Japan. [5] Therefore, more studies on anti-TNF-α agents for treatment of intestinal BD, [16] particularly information of the therapeutics effects, should be accumulated to expand the new treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] In 2015, ADa was approved for treatment of intestinal BD in Japan. [5] Therefore, more studies on anti-TNF-α agents for treatment of intestinal BD, [16] particularly information of the therapeutics effects, should be accumulated to expand the new treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Various other types of lesion have also been de- scribed, including punched-out esophageal ulcers, multiple erosions, and lesions resembling those of ulcerative colitis (8). Treatment of BD intestinal lesions includes 5aminosalicylic acid (5-ASA) formulations, prednisolone (PSL), colchicine, and various other immunosuppressive agents, including azathioprine (9). However, the clinical outcome is sometimes poor, especially in severe cases, leading to serious hemorrhaging or intestinal perforation that requires surgery in some cases (10).…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Travis et al (11) reported the efficacy of anti-TNF-α antibody-based therapy in the treatment of BD intestinal lesions. While the efficacy of infliximab (IFX) and adalimumab (ADA) in BD intestinal lesions has been demonstrated in Japan (12,13), there are only a few reports on the long-term efficacy of anti-TNF-α antibody-based therapy in BD intestinal lesions (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no objective tool for assessment of disease activity in entero-BD; therefore, it is not easy to evaluate disease activity and treatment efficacy in the clinical setting. In addition, because CS is considered for standard therapy in patients with severe symptoms and with deep ulcerative lesions [9, 10], the effectiveness of TNF-i without CS has not been well examined [11]. In the present study, we quantitatively investigated the effectiveness of 1-year treatment with TNF-i in 49 patients with entero-BD refractory to conventional therapy and compared the results to those achieved with CS without TNF-i, using the disease activity index for intestinal Behcet’s disease (DAIBD) developed in 2011 [12, 13].…”
Section: Introductionmentioning
confidence: 99%